Effect of scaling and root planing with and without adjunctive use of an essential‐oil‐based oral rinse in the treatment of periodontal inflammation in type‐2 diabetic patients. Issue 1 (7th September 2015) - Alshehri, Mohammed; Alshail, Faisal; Alshehri, Fahad Ali
Abstract: Aim: The aim was to assess the effect of scaling and root planing (SRP) with and without adjunctive use of an essential‐oil (EO)‐based oral rinse in the treatment of periodontal inflammation in type‐2 diabetic (T2D) patients. Methods: Sixty T2D patients were included. In Group 1 ( n = 30), SRP was performed and patients were instructed to rinse twice daily with EO‐based oral rinse for 30 days. In Group 2 ( n = 30), SRP was performed and participants were instructed to rinse twice daily with water for 30 days. Periodontal parameters (plaque index (PI), bleeding on probing (BOP), and probing pocket depth (PPD) ≥ 4 mm) and hemoglobin A1c (HbA1c) levels were assessed at baseline and after 90 days. Results: In both groups, periodontal parameters were similar at baseline. After 90 days of follow‐up, there was a significant reduction in the severity of periodontal parameters in patients in Group 1 compared with Group 2. After 90 days of follow‐up, there was also a significant reduction in HbA1c among patients in Group 1 compared with Group 2. Conclusions: Scaling and root planing with adjunct use of an EO‐based oral rinse is more effective in the treatment of periodontal inflammation in T2D patients than SRP alone. This approach also helps reduce hyperglycemia in T2D patients as compared with when SRP is performed alone.